Plerixafor on-demand in association with low-dose cyclophosphamide and G-CSF in the mobilization of patients with multiple myeloma: High effectiveness, low toxicity, and affordable cost. (2020) - Milone, Giuseppe; Conticello, Concetta; Leotta, Salvatore; Michieli, Maria Grazia; Martino, Massimo; Marco, Anna Lia Di; Spadaro, Andrea; Cupri, Alessandra; Condorelli, Annalisa; Milone, Giulio Antonio; Markovic, Uros; Sciortino, Roberta; et al.
Highlights: In CD34 mobilization of Multiple Myeloma patients, Cyclophosphamide at the dose of 4 gr/m2 is usually administered. A lower dose of Cyclophosphamide (1.5–2.0 gr/m2) has a lower mobilizing effect and, for this reason, this dose is not widely used in CD34+ cells mobilization. The use of Plerixafor on demand, however, could have changed these conclusions. We hypothesized that when used in conjunction with on-demand Plerixafor, low lose CTX is more advantageous than the higher dose. The results of this prospective trial support, indeed, the view that low dose Cyclophosphamide in association to on-demand PLX allows the reaching efficacy and low toxicity. Abstract: In CD34+ cells mobilization of patients with multiple myeloma (MM), the use of Cyclophosphamide (CTX) at a dose of 2 g/m 2 has low efficacy although also lower toxicity. The suboptimal mobilizing effect of low-dose CTX, however, may be overcome by plerixafor (PLX) on demand. We conducted a prospective multicenter study in 138 patients with MM to evaluate CTX 2 g/m 2 in association with granulocyte-colony stimulating factor (G-CSF) and on-demand PLX. We compared results with a historical group of MM patients (n = 138) mobilized using CTX at a dose of 4 g/m 2 . CD34+ cells greater than 2 × 10 6 /kg in max three aphereses were harvested in 98.6% of patients in the on-demand PLX study group while in 84.0% in the historical group, (p = 0.0001). In the on-demand-PLX study group, a successful harvest greater than 5 × 10 6 /kg in max three aphereses was observed in 85.5% of patients versus 62.3% of patients in the historical control group, (p=0.0001). In the on-demand-PLX study group, 4.3% (6/138) of patients had febrile complications. Salvage mobilization in the on-demand PLX study group was 1.4%. In conclusions, on-demand PLX + CTX 2 g/m2 + G-CSF 10 μg/kg has higher efficacy and lower toxicity compared with CTX 4 g/m2 + G-CSF. An analysis of costs is presented.